15-deoxy-Δ12, 14-prostaglandin J2 Down-Regulates Activin-Induced Activin Receptor, Smad, and Cytokines Expression via Suppression of NF-κB and MAPK Signaling in HepG2 Cells. (24th September 2013) - Park, Seung-Won; Cho, Chunghee; Cho, Byung-Nam; Kim, Youngchul; Goo, Tae Won; Kim, Young Il
Abstract : 15-Deoxy-Δ 12, 14 -prostaglandin J2 (15d-PGJ2 ) and activin are implicated in the control of apoptosis, cell proliferation, and inflammation in cells. We examined both the mechanism by which 15d-PGJ2 regulates the transcription of activin-induced activin receptors (ActR) and Smads in HepG2 cells and the involvement of the nuclear factor- κ B (NF- κ B) and mitogen-activated protein kinase (MAPK) pathways in this regulation. Activin A (25 ng/mL) inhibited HepG2 cell proliferation, whereas 15d-PGJ2 (2 μ M and 5 μ M) had no effect. Activin A and 15d-PGJ2 showed different regulatory effects on ActR and Smad expression, NF- κ B p65 activity and MEK/ERK phosphorylation, whereas they both decreased IL-6 production and increased IL-8 production. When co-stimulated with 15d-PGJ2 and activin, 15d-PGJ2 inhibited the activin-induced increases in ActR and Smad expression, and decreased activin-induced IL-6 production. However, it increased activin-induced IL-8 production. In addition, 15d-PGJ2 inhibited activin-induced NF- κ B p65 activity and activin-induced MEK/ERK phosphorylation. These results suggest that 15d-PGJ2 suppresses activin-induced ActR and Smad expression, down-regulates IL-6 production, and up-regulates IL-8 production via suppression of NF- κ B and MAPK signaling pathway in HepG2 cells. Regulation of ActR and Smad transcript expression and cytokine production involves NF- κ B and the MAPK pathway via interaction with 15d-PGJ2 /activin/Smad signaling.